Green Infrastructure in Urban Settings: Bringing Together the Forest and Concrete Jungle - Arun Kumar Koottharasan Nadar (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Landscape is a crucial part of any breathing space an urban area has. In this research paper, we go through a new way of looking at landscapes integrating landscape at various levels in the urban fabric integrating vegetation on upper levels which are accessible by escalators and lifts just like a metro station. Since most of the ground space has already been utilized the higher levels of urban space will be used for landscaping. these structures will be created of RCC and modern precast units. where nature will take over and vegetation will be planted. They can be worked out to imitate forests and agriculture. So there will be no bias between the prehistoric world and the modern concrete jungle. This will act as an overlap between the natural and manmade world. i.e. it will fall between the living and nonliving. The importance of research is to guide the traditional practices in a new way of looking at providing landscaping in urban areas. It will no longer be a monotonous horizon. In some places sky will be visible and in some places it won’t be. there will be levels to it. Most visibility will be at the higher levels.